Paracoccidioides brasilinsis-Induced Migration of Dendritic Cells and Subsequent T-Cell Activation in the Lung-Draining Lymph Nodes - Silvana dos Santos, Suelen (Public Library of Science, 2011)
Paracoccidioidomycosis is a mycotic disease caused by a dimorphic fungus, Paracoccidioides brasiliensis (Pb), that starts with inhalation of the fungus; thus, lung cells such as DC are part of the first line of defense against this microorganism. Migration of DC to the lymph nodes is the first step in initiating T cell responses. The mechanisms involved in resistance to Pb infection are poorly understood, but it is likely that DC play a pivotal role in the induction of effector T cells that control Pb infection. In this study, we showed that after Pb Infection, an important modification of lung DC receptor expression occurred. We observed an increased expression of CCR7 and CD103 on lung DC after infection, as well as MHC-II. After Pb infection, bone marrow-derived DC as well lung DC, migrate to lymph nodes. Migration of lung DC could represent an important mechanism of pathogenesis during PCM infection. In resume our data showed that Pb induced DC migration. Furthermore, we demonstrated that bone marrow-derived DC stimulated by Pb migrate to the lymph nodes and activate a T helper (Th) response. To the best of our knowledge, this is the first reported data showing that Pb induces migration of DC and activate a T helper (Th) response.